Acceptance of digital health in Portugal: An example of digital divide - Lima, M. L.; Camilo, C.; Rodrigues, R. B.; Bobrowicz-Campos, E.; Espanha, R.; Martins, H.; Sánchez-García, J. (Portuguese Journal of Public Health, 2025)
Introduction: Digital health technologies are becoming increasingly important in achieving broader healthcare goals worldwide, with significant investments in infrastructure and legislative frameworks to regulate this growing sector. However, despite substantial structural support, a gap remains between investment and consumer usage, particularly evident in Portugal. Methods: This study aims to understand attitudes and behaviors toward digital health among the Portuguese population and identify key variables influencing their adoption. Utilizing the Technology Acceptance Model, sociodemographic and subjective factors were examined in a national online survey, part of the CROss-National Online Survey 2 panel associated with the European Social Survey Round 10. Results: The results indicate a positive perception of digital health technologies, with high scores for perceived ease of use (M = 4.97, SD = 1.18) and for the value attributed to these tools (M = 4.71, SD = 1.14). However, their actual use remains relatively low (M = 1.23, SD = 0.94), with concerns about the quality of care and dependence on technology (M = 4.01, SD = 0.94). Older people perceived less ease of use of digital health tools (r = −0.234, p < 0.01), along with less favorable attitudes (r = −0.195, p < 0.01) and lower intention to use them (r = −0.145, p < 0.01). In contrast, literacy, income and education level were positively associated with the above dimensions, highlighting the digital health divide. While digital health technologies offer promising opportunities, it is essential to address their potential to exacerbate health inequalities. Conclusions: This study underscores the significance of understanding sociodemographic and subjective factors in shaping attitudes and behaviors toward digital health. The implications of the findings for policy and intervention aiming to enhance digital healthcare engagement and accessibility are discussed, including the implementation of targeted national digital health literacy programs and the integration of digital health education into formal education curricula.